distinguish test of health promotion media toward skin diseases prevention - zahara, amalina; setyaningsih, yuliani; suroto, suroto (Universitas Respati Yogyakarta, 2019)
Garbage transport officer risky for skin disease cause direct contact with various types of trash. A skin disease worsening the condition could reduce productivity and health if not addressed seriously because it is very disturbing for the convenience of patients. The aim of this study was to compare health promotion with lecture and poster on the knowledge and attitudes of skin diseases preventionThis study was a quasy-experimental with pre-post test two group design. Total subjects was 32 divided into 2 groups, namely speech group and poster group. Lecture intervention was given twice, which is lecture and lecture with forum group discussion (FGD). Interventions using posters are given for 2 weeks. Knowledge and attitude about prevention of disease skin obtained from questionnaire before and after education. Effect of disease skin prevention on knowledge and attitude in both groups were tested used Mann-Whitney and Wilcoxon.There was an increase in knowledge of skin diseases prevention in the lecture group (p-value=<0,001) and poster groups (p-value=0,257), but there was no increase in attitude in both group. There was a difference between post-test scores skin diseases prevention knowledge in speech and poster group (p<0,05). However, there was no difference in attitude changing in both groups.The results revealed that health promotion with lecture dan poster media can affect in knowledge garbage transport officer of skin diseases prevention. Lecture was more effective at increasing knowledge than poster media